Understanding the importance of sediments to water ouality in coastal shallow lagoons - Brito, Ana (2012)
The undesirable enrichment of water by nutrients may be a problem, especially in areas with restricted exchange with the sea. The tidal regime flushes the system and contributes for the removal of phytoplankton, favouring phytobenthos as the target of enhanced nutrients. Water samples were collected during the years of 2006 and 2007-08 for nutrients, chlorophyll a and dissolved oxygen. Sediment sample s were also collected for pore water nutrients and benthic chlorophyll a. From comparison with previous work, a decrease in the nitrogen concentration in the water column can be pointed out, which may indicate an improvement of the water quality. Pore water DAIN represents approximately 75% of the total DAIN of the whole lagoon. Benthic chlorophyll a concentrations were much larger than in the water column, representing around 99% of the total chlorophyll existent in the lagoon. Benthic microalgae play a relevant role in this system and therefore standard monitoring programs of the WFD, which do not consider this component, may fail to track nutrient-driven changes in primary producers. Dissolved oxygen concentration could be near critical levels during the summer (early in the morning), especially in the inner channels.